Exercise pretraining protects against cerebral ischaemia induced by heat stroke in rats. Issue 9 (11th May 2007) - Chen, Yu-Wen; Chen, Sheng-Hsien; Chou, Willy; Lo, Yi-Ming; Hung, Ching-Hsia; Lin, Mao-Tsun
Abstract : Background: In the rat brain, heat-stroke-induced damage to cerebral neurons is attenuated through heat-shock-induced overexpression of heat-shock protein 72 (HSP72). Objective: To ascertain whether progressive exercise preconditioning induces HSP72 expression in the rat brain and prevents heat-stroke-induced cerebral ischaemia and injury. Methods: Male Wistar rats were randomly assigned to either a sedentary group or an exercise group. Those in the exercise group progressively ran on a treadmill 5 days/week, for 30–60 min/day at an intensity of 20–30 m/min for 3 weeks. The effects of heat stroke on mean arterial pressure, cerebral blood flow, brain ischaemia markers (glutamate, lactate/pyruvate ratio and nitric oxide), a cerebral injury marker (glycerol) and brain neuronal damage score in the preconditioned animals were compared with effects in unexercised controls. Heat stroke was induced by exposing urethane-anaesthetised animals to a temperature of 43°C for 55 min, which caused the body temperature to reach 42°C. Results: Three weeks of progressive exercise pretreatment induced HSP72 preconditioning in the brain and conferred significant protection against heat-stroke-induced hyperthermia, arterial hypotension, cerebral ischaemia and neuronal damage; it also prolonged survival. Conclusions: Exercise for 3 weeks can improve heat tolerance as well as attenuate heat-stroke-induced cerebral ischaemia in rats. The maintenance of mean arterial pressure and cerebral blood flow at appropriate levels in the rat brain may be related to overexpression of HSP72.